Oreocharis wumengensis, a new species of Gesneriaceae from northeastern Yunnan, China - Cai, Lei (PhytoKeys, 2020)
A new species of Gesneriaceae, Oreocharis wumengensis Lei Cai & Z.L.Dao from Wumeng Mountain area, Yanjin County, Yunnan Province, China, is described. The new species is morphologically similar to O. panzhouensis Lei Cai, Y.Guo & F.Wen in the shape of corolla, number of stigma and stamens, but it can be easily distinguished from this species by the leaf shape and indumentum characters of leaf blade, calyx and stamens. Detailed descriptions with photographs of the plant and holotype, and comparisons with morphologically similar species, are also provided.